Glycopolymer Inhibitors of Galectin-3 Suppress the Markers of Tissue Remodeling in Pulmonary Hypertension - Sedlář, Antonín; Vrbata, David; Pokorná, Kateřina; Holzerová, Kristýna; Červený, Jakub; Kočková, Olga; Hlaváčková, Markéta; Doubková, Martina; Musílková, Jana; Křen, Vladimír; Kolář, František; Bačáková, Lucie; et al. (Journal of medicinal chemistry, 2024)
Pulmonary hypertension is a cardiovascular disease with a low survival rate. The protein galectin-3 (Gal-3) binding β-galactosides of cellular glycoproteins plays an important role in the onset and development of this disease. Carbohydrate-based drugs that target Gal-3 represent a new therapeutic strategy in the treatment of pulmonary hypertension. Here, we present the synthesis of novel hydrophilic glycopolymer inhibitors of Gal-3 based on a polyoxazoline chain decorated with carbohydrate ligands. Biolayer interferometry revealed a high binding affinity of these glycopolymers to Gal-3 in the subnanomolar range. In the cell cultures of cardiac fibroblasts and pulmonary artery smooth muscle cells, the most potent glycopolymer 18 (Lac-high) caused a decrease in the expression of markers of tissue remodeling in pulmonary hypertension. The glycopolymers were shown to penetrate into the cells. In a biodistribution and pharmacokinetics study in rats, the glycopolymers accumulated in heart and lung tissues, which are most affected by pulmonary hypertension.
Keywords: galektin 3; tkáňová distribuce; Male; fibroblasty; biologické markery; arteria pulmonalis; Fibroblasts; Biomarkers; Tissue Distribution; Pulmonary Artery; Hypertension, Pulmonary; Galectin 3; mužské pohlaví; Polymers; krysa rodu Rattus; kultivované buňky; Animals; lidé; polymery; Humans; zvířata; Rats; Cells, Cultured; plicní hypertenze